Kowanin, Suatu Santon dari Kulit Batang Garcinia cowa Roxb - ', Darwati; Bahti, Husen H; ', Supriyatna; ', Dachriyanus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
The compound tetraoxygenated xanthone was isolated from the crude extract of the stem bark of Garcinia cowaRoxb. The compound tetraoxygenated xanthone was caried out as yellow crystal with melting point 136-1370C.The structure of this compound was detremined base on spectroscopic methods, including UV, IR, 1H-NMR,13C-NMR 1D and 2D. The compound was found to exhibit cytotoxicity against T47D cell by SRB method